Interpersonal Communication of Parents to Children in Restricting the Use of the TikTok Application in Sidoarjo Regency - Dwi Irmawati; Nur Maghfirah Aesthetika (Indonesian Journal of Cultural and Community Development, 2022)
TikTok is a social media application that invites its users to create short videos that are about 15 seconds long accompanied by music, filters, and also several other features. TikTok was created by a Chinese company, namely China ByteDance in 2016. The use of TikTok in children aged 10-12 years is very interesting to be used as research material. This study aims to determine the interpersonal communication of parents to children in limiting the use of the TikTok application in the village of Cemengkalang Sidoarjo. This study has several indicators, namely selective, systemic, unique, processual, and transactional. This research was conducted on five residents of Cemengkalang village, Sidoarjo. Researchers used descriptive qualitative research methods with data collection in the form of in-depth interviews with informants. In this study using the theory of Interpersonal Communication from Julia T. Wood. The data that researchers can show that in limiting the use of TikTok parents participate in accompanying children when playing TikTok this is done so that parents can select the video content that children see when playing TikTok, besides that parents also limit the use of the TikTok application for every day, parents establish close relationships with children and often give messages to children not to play TikTok too often.